2018
DOI: 10.1007/s00213-018-5066-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic cathinone adulteration of illegal drugs

Abstract: Rationale.-Current prevalence estimates of synthetic cathinone ("bath salts") use may be underestimates given that traditional metrics (e.g., surveys, urinalysis) often fail to capture the emergent issue of synthetic cathinone adulteration of more common illegal drugs such as ecstasy (3,4-methylenedioxymethamphetamine).Objectives.-This review examines the evolution of synthetic cathinones and prevalence of use over the past decade in the United States. We also review methods of self-report and biological testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 66 publications
1
37
0
1
Order By: Relevance
“…These mainly include synthetic stimulants, depressants, hallucinogens, and cannabinoids (EMCDDA, 2017;Nelson, Bryant, & Aks, 2014), but some plant-based drugs may also be classified as NPS (Schifano, Orsolini, Duccio Papanti, & Corkery, 2015). In cases where sales information or labels exist, these may be inaccurate or misleading due to intended mislabeling or adulteration of common drugs with NPS (Oliver et al, 2019;Palamar et al 2017;Scherbaum, Schifano, & Bonnet, 2017;UNODC, 2016) or the chemical name may be difficult to remember. Hence, even when reporting to the best of their knowledge, users may still do so incorrectly.…”
Section: Introductionmentioning
confidence: 99%
“…These mainly include synthetic stimulants, depressants, hallucinogens, and cannabinoids (EMCDDA, 2017;Nelson, Bryant, & Aks, 2014), but some plant-based drugs may also be classified as NPS (Schifano, Orsolini, Duccio Papanti, & Corkery, 2015). In cases where sales information or labels exist, these may be inaccurate or misleading due to intended mislabeling or adulteration of common drugs with NPS (Oliver et al, 2019;Palamar et al 2017;Scherbaum, Schifano, & Bonnet, 2017;UNODC, 2016) or the chemical name may be difficult to remember. Hence, even when reporting to the best of their knowledge, users may still do so incorrectly.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the extent of use of new or emerging drugs can guide public health efforts, particularly those targeting synthetic cannabinoids and synthetic cathinones—two of the most commonly used classes of NPS associated with tens of thousands of poisonings in the United States as evidenced by survey, Poison Control, and emergency department data. Even though prevalence of use of synthetic cannabinoids and synthetic cathinones has decreased in recent years (Kann et al, ; Miech et al, ; Oliver et al, ), these compounds continue to emerge at an alarming rate (European Monitoring Centre for Drugs and Drug Addiction, ). Moreover, some of these compounds are highly potent and dangerous (Dalton, Wang, & Zavitsanou, ; Watterson & Olive, ), leaving users at risk for dependence or other serious adverse outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that although prevalence of (known) use of Flakka or other "bath salts" among adolescents is relatively rare, surveys likely underestimate use because these compounds are often used unknowingly as adulterants in drugs such as ecstasy in the US (Oliver et al, 2018). For example, a recent study that saliva-tested EDM festival attendees in Florida found that 30% of ecstasy users tested positive for "bath salts", including some cases of unknown Flakka exposure (Krotulski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%